Brief communication: Cineradiographic analysis of the chimpanzee (Pan troglodytes) talonavicular and calcaneocuboid joints. Issue 4 (14th May 2014) - Thompson, Nathan E.; Holowka, Nicholas B.; O'Neill, Matthew C.; Larson, Susan G.
ABSTRACT During terrestrial locomotion, chimpanzees exhibit dorsiflexion of the midfoot between midstance and toe‐off of stance phase, a phenomenon that has been called the "midtarsal break." This motion is generally absent during human bipedalism, and in chimpanzees is associated with more mobile foot joints than in humans. However, the contribution of individual foot joints to overall foot mobility in chimpanzees is poorly understood, particularly on the medial side of the foot. The talonavicular (TN) and calcaneocuboid (CC) joints have both been suggested to contribute significantly to midfoot mobility and to the midtarsal break in chimpanzees. To evaluate the relative magnitude of motion that can occur at these joints, we tracked skeletal motion of the hindfoot and midfoot during passive plantarflexion and dorsiflexion manipulations using cineradiography. The sagittal plane range of motion was 38 ± 10° at the TN joint and 14 ± 8° at the CC joint. This finding indicates that the TN joint is more mobile than the CC joint during ankle plantarflexion–dorsiflexion. We suggest that the larger range of motion at the TN joint during dorsiflexion is associated with a rotation (inversion–eversion) across the transverse tarsal joint, which may occur in addition to sagittal plane motion. Am J Phys Anthropol 154:604–608, 2014. © 2014 Wiley Periodicals, Inc.